The Grateful Dead - Anthem to Beauty - Marre, Jeremy (Classic Albums: The Grateful Dead - Anthem to Beauty)
The Grateful Dead are a unique phenomenon. One of the most successful live touring bands in the world, their longevity is founded on their desire to play music their way, coupled with an extraordinarily close relationship to their huge following. From "Anthem to Beauty" tells the story of the band and their journey from the experimental "Anthem of the Sun" (recorded in 1967/1968) to the accessible, countryish "American Beauty." It is told in the band's own words and includes a rare interview with lyricist Robert Hunter. The film also features a wealth of rare vintage film footage of the Grateful Dead in their prime, including television appearances, home videos, and classic recordings like "Ripple," "Box of Rain," "Truckin'," and "Mountains of the Moon," and it all adds up to a riveting portrait of one of the rock world's most controversial bands. [www.amazon.com]